PENGARUH PARTISIPASI PENGANGGARAN, ASIMETRI INFORMASI DAN BUDAYA ORGANISASI PADA SENJANGAN ANGGARAN (STUDI KASUS PADA PATRA HOTELS & RESORTS) - Glory Koeswardhana; Saprudin Saprudin (Journal of Information System, Applied, Management, Accounting and Research, 2019)
This research aims to know the influence of Participation in Budgeting, Information Asymmetry, and Organizational Culture in the Budgetary Slack in PATRA HOTELS & RESORTS. To be able to achieve that goal used linear regression data analysis techniques double, F -test and t- test. Methods of collecting data in this study using a questionnaire that was distributed to the Manager, Supervisor and Budget Staff at PATRA HOTELS & RESORTS. Based on the results of analysis of the mind that simultaneously (a) Variable Budgeting Participation, Information Asymmetry and Organizational Culture significantly to Budgetary Slack, partially variable and (b) the Budgeting Participation of a significant negative effect on Budgetary Slack PATRA HOTELS & RESORTS (c) Asymmetry of Information of significant positive effect on the Budgetary Slack PATRA HOTELS & RESORTS and (d) Organizational Culture positive significant effect on Budgetary Slack PATRA HOTELS & RESORTS.